Education and Gender - Dhar, Debotri (Education as a humanitarian response., 2014)
Education and Gender draws on international research from the USA, the UK, India, Mexico, Sub-Saharan Africa and the Caribbean, to provide a comprehensive global overview of the relationship between gender and education. Rooting constructions of gender and sexuality in specific geographical contexts, the contributors consider a range of issues. Themes discussed include the gender gap in educational attainment; pedagogical strategies; stereotyping in curricula; and education policy. Drawing on best practices worldwide, the contributors identify the current gaps and propose solutions to promote.